Genome-Wide Identification, Characterization and Expression Profiling of Potato (Solanum tuberosum) Frataxin (FH) Gene - Kurt, Firat; Filiz, Ertugrul; Yildiz, Kubra; Akbudak, M. Aydin (Mdpi, 2023)
Frataxin (FH) plays a crucial role in the biogenesis of mitochondria and the regulation of iron in the cells of various organisms. However, there has been very little research on FH in plants. In this study, the potato FH gene (StFH) was identified and characterized using a genome-wide approach, and its sequence was compared to those of FH genes from Arabidopsis, rice, and maize. The FH genes were found to have a lineage-specific distribution and were more conserved in monocots than in dicots. While multiple copies of FH genes have been reported in some species, including plants, only one isoform of FH was found in potato. The expression of StFH in leaves and roots was analyzed under two different abiotic stress conditions, and the results showed that StFH was upregulated more in leaves and that its expression levels increased with the severity of the stress. This is the first study to examine the expression of an FH gene under abiotic stress conditions.
Keywords: Frataxin; Mitochondria; Iron Homeostasis; Sulfur; Transcription Factors; Co-Expression; Transcription Factors; Abscisic-Acid; Arabidopsis-Thaliana; Drought Tolerance; Oxidative Stress; Iron-Binding; Nitric-Oxide; Salt Stress; Plant; Prediction